Air-void-affected zone in concrete beam under four-point bending fracture - Zhang, Chuanchuan; Yang, Xinhua; Gao, Hu (Journal of Civil Engineering and Management, 2018)
A series of numerical simulations were performed on prenotched four-point bending (FPB) concrete beams containing air voids of different sizes and locations by using the finite element method combined with the cohesive crack model. The void-affected zone was proposed for characterizing the effect of a void on a fracture, and its size was determined by moving an air void horizontally until the crack path changed. As a function of air void location and size, the dimensionless affected-zone radius was fitted according to the numerical results. Finally, the fracture processes of the pre-notched FPB concrete beams with randomly distributed voids were simulated numerically, and the affected-zone radius was used to explain the choice of crack paths to verify the prediction. It was found that the prediction is accurate for an isolated affected zone and is roughly approximate for an overlapped one.